2014
DOI: 10.7554/elife.02671
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of retinal axon growth by secreted Vax1 homeodomain protein

Abstract: Retinal ganglion cell (RGC) axons of binocular animals cross the midline at the optic chiasm (OC) to grow toward their synaptic targets in the contralateral brain. Ventral anterior homeobox 1 (Vax1) plays an essential role in the development of the OC by regulating RGC axon growth in a non-cell autonomous manner. In this study, we identify an unexpected function of Vax1 that is secreted from ventral hypothalamic cells and diffuses to RGC axons, where it promotes axonal growth independent of its transcription f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 48 publications
2
60
0
Order By: Relevance
“…Mice lacking Vax1 died perinatally, although some survived after birth (Bertuzzi et al 1999;Hallonet et al 1999), exhibiting cleft palate and coloboma due to the failure of optic fissure closure. In addition, these animals were unable to develop the optic chiasm and presented with axon guidance defects in the form of retinal ganglion cells whose axons were unable to properly localize within the brain (Kim et al 2014). Kim et al (2014) suggested that, in addition to its function as a transcription factor, Vax1 may also work as a secreted protein to promote the growth of retinal ganglion cells towards the brain.…”
Section: Vax1 (Ventral Anterior Homeobox 1)mentioning
confidence: 99%
“…Mice lacking Vax1 died perinatally, although some survived after birth (Bertuzzi et al 1999;Hallonet et al 1999), exhibiting cleft palate and coloboma due to the failure of optic fissure closure. In addition, these animals were unable to develop the optic chiasm and presented with axon guidance defects in the form of retinal ganglion cells whose axons were unable to properly localize within the brain (Kim et al 2014). Kim et al (2014) suggested that, in addition to its function as a transcription factor, Vax1 may also work as a secreted protein to promote the growth of retinal ganglion cells towards the brain.…”
Section: Vax1 (Ventral Anterior Homeobox 1)mentioning
confidence: 99%
“…This classical role of homeodomain transcription factors has been challenged by the fact that homeoproteins can also act non-cell-autonomously by a mechanism involving secretion and intracellular transfer into neighboring cells (Prochiantz and Di Nardo, 2015). Recently, these disparate results were confirmed: Vax1 is secreted by ventral hypothalamic cells and binds to a heparan sulfate proteoglycan (HSPG) expressed on retinal axons and is internalized into retinal growth cones where it activates locally protein synthesis to promote axonal growth (Kim et al, 2014) (Fig. 1).…”
Section: Molecular Cues For Axon Growthmentioning
confidence: 99%
“…VAX1 contains four exons and encodes a protein with DNA-binding paired-type homeodomain [272]. Vax1 protein can be secreted and penetrate into axons of RGC and other neurons [273].…”
Section: Vax1mentioning
confidence: 99%
“…In Danio rerio, Vax1 is expressed in the ventral portion of the developing eye [277]. It was discovered that Vax1 is secreted from ventral hypothalamic cells and diffuses to RGC axons, where it promotes axonal growth [273]. Microphthalmia associated with cleft lip and palate and agenesis of the corpus callosum caused by homozygous mutation in the Vax1 gene was reported [278].…”
Section: Vax1mentioning
confidence: 99%